Microbiological assessment of raw milk available in the metropolitan city of Sindh, Karachi - Pakistan: Microbiological Assessment of Raw Milk - Zaheer Abbas, Sayed; Naseem Khan, Muhammad; Zehra Naqvi, Anjum; Tabassum, Nargis; Ali Mirani, Zulfiqar; Basit Khan, Abdul; Ali, Razim (Pakistan Journal of Health Sciences, 2022)
Currently, milk quality is judge on its health and hygienic parameters equally as its composition. Raw milk is a rich medium for the growth and proliferation of different pathogenic microorganisms such food-safety hazard may incorporate into the dairy chain, not only affect its safety and quality but also cause various milk borne diseases. Objective: To evaluate the microbiological assessment of raw milk accessible in Karachi with the intention to develop risk tracking strategies and its mitigation plan in future. Methods: Total 270 raw milk samples were collected from different sites throughout the dairy supply chains in each district of the city. Microbiological assessment of raw milk was carried out by following the bacteriological analytical manual (BAM, FDA) protocol. Results: The raw milk safety and quality at the dairy farms were satisfied, except raw milk storage tanks samples. The bacterial count boosted in almost all the samples collected during its transportation, higher aerobic and pathogenic load was observed in the retail shop’s samples however, maximum counts were noticed in the selling point milk samples. None of the milk samples contained other pathogens like Listeria or Salmonella. Conclusions: The milk quality of the supply chain, retail shops and storage tanks at dairy farms were un-satisfied based on different microbiological parameters.